Parental Ethno theories of two groups of Chinese immigrants: a perspective from migration. (4th May 2019) - Zheng, Lijie; De Haan, Mariëtte; Koops, Willem
ABSTRACT: This paper argues against the stereotypical image of the Chinese parent by studying how two groups of Chinese immigrant mothers, economic and knowledge immigrants, rebuilt their parenting ethnotheories after migration to the Netherlands. The results show that economic immigrants believe in natural growth and direct their children through authoritarian relationships, while knowledge immigrants see parenting as a task which demands much personal effort and an equal, transparent and close parent–child relationship. These differences are explained through a focus on both their pre-migration histories and how these are reinterpreted in the migration context.